Penghapusan Denda Pajak Terhadap Kepatuhan Driver Online Membayar Pajak Kendaraan Bermotor Masa Pandemi - Naftaly Patria Amazia (Jurnal Akuntansi, 2022)
Taxpayer Compliance especially during pandemic become a quite serious problem due to a decreasing of economy in every sector, specifically for taxpayers who has unstable income such as online driver. This research aims to measure whether the administration tax fine waiver policy has an effect on the compliance of online drivers to pay the vehicle taxes during pandemic. In this research, the method used is quantitative research. Sample accumulation technic used is purposive sampling. The number of respondents used in this research is 100 respondents consisting of motorized vehicle taxpayers who work as online drivers. The analytical method used in this research is simple regression analysis. The result of this research shows that the administration tax fine waiver policy has an effect on the compliance of online drivers to pay the vehicle tax during pandemic. The conclusion of the research is if the administration tax fine waiver has a good effect for motorized vehicle taxpayers (online drivers) so the taxpayer compliance (online drivers) to pay the motorized vehicle tax will be increasead.Keywords: Administration Tax Fine Waiver, Tax Compliance, Vehicle Tax